Case report: Duplication of the GCK gene is a novel cause of nesidioblastosis: evidence from a case with Silver-Russell syndrome-like phenotype related to chromosome 7 - Shoji, Takashi; Yamauchi, Ichiro; Kawasaki, Hidenori; Iwanaga, Kogoro; Hakata, Takuro; Tanaka, Daisuke; Fujikura, Junji; Masui, Toshihiko; Suzuki, Hisato; Yamada, Mamiko; Kosaki, Kenjiro; Kasai, Yosuke; et al. (Frontiers in Endocrinology, 2024)
Silver-Russell syndrome (SRS) is a syndrome characterized by prenatal and postnatal growth retardation, facial features, and body asymmetry. SRS is often complicated with hypoglycemia, whose etiology is unclear. We describe the clinical course of 25-year-old man with hypoglycemia. We diagnosed him with hyperinsulinemic hypoglycemia (HH) and treated him with laparoscopic distal pancreatectomy. Histological examination led to a diagnosis of nesidioblastosis. The juvenile onset of his nesidioblastosis and its slowly progressive course suggested a genetic etiology. Whole-exome sequencing (WES) identified the heterozygous NR0B2 Ala195Ser variant, which alone was unlikely to cause nesidioblastosis because this variant is sometimes detected in the Japanese population. Copy number analysis using WES data suggested duplication in chromosome 7, and subsequent G-banding chromosome analysis confirmed mos dup(7)(p11.2p14). We determined that the patient had SRS-like phenotype based on his clinical features and this duplication. Furthermore, we found that the duplicated region contained the GCK gene, whose gain-of function variants could cause HH. Taken together, the patient’s HH may have been caused by duplication of the GCK gene, which could be a novel cause of nesidioblastosis.